2016
DOI: 10.3926/ic.837
|View full text |Cite
|
Sign up to set email alerts
|

High involvement work programs (HIWP) measurement model validation and its capacity to predict perceived performance

Abstract: Our study confirms significant (although low) relationship between the use of HIWP and performance. But nevertheless, part of measurement model has not been fully validated and should be confirmed in future research.-1308-Intangible Capital -http://dx.doi.org/10.3926/ic.837Research limitations/implications: First, our data come from studies of more than 15 years ago, but to test measurement models, the date of the data is not a significant limitation because we analyzed the relationship between the constructs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In addition, another subsample of 590 people were asked if they had participated in the following programs to promote CI in the past 12 months (Juarez Tarraga et al, 2016): suggestion boxes, permanent team suggestion systems, short-term team suggestion systems, and self-directed work teams. Thus, for each of these people, we calculated the number of programs they had participated in (ranging from 0 to 4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another subsample of 590 people were asked if they had participated in the following programs to promote CI in the past 12 months (Juarez Tarraga et al, 2016): suggestion boxes, permanent team suggestion systems, short-term team suggestion systems, and self-directed work teams. Thus, for each of these people, we calculated the number of programs they had participated in (ranging from 0 to 4).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, for each of these people, we calculated the number of programs they had participated in (ranging from 0 to 4). This scale was previously used by Marin-Garcia et al (2018), based on the works of Drehmer et al (2000), Lawler et al (2001), Juarez Tarraga et al (2016), and Guerrero and Barraud-Didier (2004). Because the questions we ask are fairly objective and refer to four different exposures to easily identifiable CI programs, we think recall bias is not likely.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of these practices is to empower workers to make better decisions by improving their training, providing them with the information and knowledge they need to do their jobs properly and rewarding them for it (Boxall and Winterton, 2018). Many authors have found a positive relationship between HIWS and operational, perceived performance, financial and even human resource improvements in organizations in different sectors (Conci, 2012; Kilroy et al , 2017; Juarez-Tarraga et al , 2016).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…All the first-order variables are reflective, which means that the items measure aspects of the latent variables. The PIRK systems is a second-order formative construct created from the first-order variables of empowerment, communication, rewards system and training, which were measured with reflective items (Juarez-Tarraga et al , 2016; Sarstedt et al , 2019). On this view of the systems, power, information, rewards and knowledge are the dimensions of the systems, and they can be aggregated into a single higher order variable named PIRK systems.…”
Section: Empirical Studymentioning
confidence: 99%
“…These tools have been gradually introduced into companies and have been used in different ways by applying distinct indicators to assess their performance (Juarez-Tarraga et al , 2016; Marin-Garcia, 2013b); for instance, the programs that first appeared in firms were suggestion systems, followed by quality circles, and later improvement teams were introduced (García-Lorenzo and Prado, 2003; Marin-Garcia, Bonavia Martin, and Miralles, 2008). In a study of Spanish firms with more than 25 workers, the degree to which these systems are used clearly inclines toward improvement teams (present in 74 percent of firms) and suggestions systems (present in 64 percent of firms), whereas quality circles are becoming less common (30 percent of firms) (García-Lorenzo and Prado, 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%